Hysteresis Induced by Incomplete Cationic Redox in Li‐Rich 3d‐Transition‐Metal Layered Oxides Cathodes. Issue 23 (6th June 2022) - Fang, Liang; Zhou, Limin; Park, Mihui; Han, Daseul; Lee, Gi‐Hyeok; Kang, Seongkoo; Lee, Suwon; Chen, Mingzhe; Hu, Zhe; Zhang, Kai; Nam, Kyung‐Wan; Kang, Yong‐Mook
Abstract: Activation of oxygen redox during the first cycle has been reported as the main trigger of voltage hysteresis during further cycles in high‐energy‐density Li‐rich 3d‐transition‐metal layered oxides. However, it remains unclear whether hysteresis only occurs due to oxygen redox. Here, it is identified that the voltage hysteresis can highly correlate to cationic reduction during discharge in the Li‐rich layered oxide, Li1.2 Ni0.4 Mn0.4 O2 . In this material, the potential region of discharge accompanied by hysteresis is apparently separated from that of discharge unrelated to hysteresis. The quantitative analysis of soft/hard X‐ray absorption spectroscopies discloses that hysteresis is associated with an incomplete cationic reduction of Ni during discharge. The galvanostatic intermittent titration technique shows that the inevitable energy consumption caused by hysteresis corresponds to an overpotential of 0.3 V. The results unveil that hysteresis can also be affected by cationic redox in Li‐rich layered cathodes, implying that oxygen redox cannot be the only reason for the evolution of voltage hysteresis. Therefore, appropriate control of both cationic and anionic redox of Li‐rich layered oxides will allow them to reach their maximum energy density and efficiency. Abstract : A key question regarding the real‐world application potential of Li‐rich layered cathodes is whether the low energy efficiency associated with voltage hysteresis can be improved. The incomplete reduction of Ni acts as a main reason for the hysteresis in Li1.2 Ni0.4 Mn0.4 O2, implying that low energy efficiency caused by hysteresis cannot be unraveled only by preventing oxygen redox.